Role of hyperglucagonemia in catabolism associated with type 1 diabetes: effects on leucine metabolism and the resting metabolic rate - Charlton, M R; Nair, K S (Diabetes (New York, N.Y.), 1998)
Role of hyperglucagonemia in catabolism associated with type 1 diabetes: effects on leucine metabolism and the resting metabolic rate. M R Charlton and K S Nair Endocrine Research Unit, the Mayo Clinic and Foundation, Rochester, Minnesota 55905, USA. Abstract The catabolic state of poorly controlled type 1 diabetes has largely been attributed to insulin deficiency. However, the role of hyperglucagonemia, which occurs concomitantly with insulin deficiency, has not been fully investigated. We studied the effects of hyperglucagonemia during insulin deprivation on energy expenditure (using indirect calorimetry) and protein metabolism (using L-[1-(13)C,15N]leucine and L-[1-(13)C]leucine as tracers) in 12 type 1 diabetic subjects. Five protocols were used: insulin treatment, insulin deprivation, insulin deprivation with suppression of endogenous glucagon with somatostatin (SRIH) and growth hormone replacement, insulin deprivation with endogenous glucagon suppression with SRIH (no growth hormone replacement), and insulin deprivation with SRIH and a high level of glucagon replacement (no growth hormone replacement). It was observed that leucine oxidation and the resting metabolic rate (RMR) were significantly lower during insulin treatment and insulin deprivation with concomitant SRIH infusion (lowering glucagon) than during insulin deprivation alone. Replacement of glucagon at a high level during SRIH infusion in the insulin-deprived state increased leucine oxidation and the RMR. Hyperglucagonemia was also associated with a trend for decreased protein synthesis. Hyperglucagonemia did not affect leucine transamination. Insulin replacement decreased leucine flux and oxidation. Leucine oxidation (R2 = 0.79) and the RMR (R2 = 0.81) were seen, by multiple regression analysis, to correlate with glucagon levels and not with other hormones. We conclude that while insulin deficiency increases protein breakdown, hyperglucagonemia is primarily responsible for the increased leucine oxidation and RMR seen during insulin deprivation.